EFEKTIVITAS PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN SOFTWARE AUTORUN UNTUK MENINGKATKAN KOMPETENSI FISIKA SISWA SMK NEGERI 1 PADANG - Usmeldi, Usmeldi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Physics is one of the adaptive subjects in Vocational High School (SMK). Preliminary surveys of the implementation of learning physics at SMK Negeri 1 Padang shows that many students have not mastered the abstract concepts of physics, so students find it difficult  to apply them in relevant pro-ductive subjects. Therefore, it is implemented physics learning with interactive learning media. This study aims to determine the effectiveness of interactive learning media to improve the student compe-tence. The study used a quasi experimental method with a pretest-posttest control group design. The subjects of the research were students of eleventh grade in electrical engineering expertise program at SMK Negeri 1 Padang. Data were collected by using observation sheet, achievement test, and ques-tionnaire of student responses to the implementation of learning. The result of the research shows that physics learning with interactive learning media is effective to improve the studentsâ competence, in terms of (1) students learning mastered has been achieved, (2) improvement of physics concept of ex-perimental class in medium category, (3) The average score of mastery of the physics concept of the experimental class is higher than the control class, (4) most of the experimental class students stated that the implementation of physics learning with interactive learning media is good. Suggestion to physics teacher to conduct the computer assisted learning with interactive media.